Should Antitrust Go Beyond “Antitrust”? - Brennan, Timothy J. (Sage, 2018)
Numerous observers, from all sides of the political spectrum, have proposed alternatives to economic efficiency as objectives for antitrust enforcement and decisions. A list includes fairness, inequality, labor share of income, jobs, effect on competition (apart from consumer welfare), consumer choice, promoting democracy, concentration of political power, globalization, domestic control over resources, media veracity, environmental protection, managerial competence, and mitigating consumer error. Three factors raise general doubts about the merits of doing so. One is that antitrust is sufficiently complex and that adding additional factors to balance may make it even less comprehensible to the general public (and even experts). A second is that other policies are available to pursue these alternatives that are both better designed to do so and are not subject to the vagary of whether a particular firm or sector might be involved in an antitrust violation. The third is that antitrust ought not be distracted from its economic efficiency mission, since there is no other economy wide tool for promoting economic efficiency. Those considerations and others are used to assess the potential effectiveness of incorporating each of these alternatives into antitrust enforcement and adjudication. Many of these alternatives may be a side benefit of antitrust enforcement, but not a factor that antitrust enforcers and courts can be expected to sensibly trade off against economic efficiency.
Keywords: antitrust; objectives; fairness; inequality; economic efficiency